2014
DOI: 10.17718/tojde.43009
|View full text |Cite
|
Sign up to set email alerts
|

Exploration Of Problematic Internet Use And 
Loneliness Among Distance Education Students

Abstract: The current study investigated the relationship between problematic Internet use and levels of loneliness among 311 distance education students. "The Problematic Internet Use Scale" and "UCLA-Loneliness Scale III" were used to collect the data. Independentsamples t-test and one-way ANOVA were conducted to examine the differences; and correlation and regression analyses were used to examine the relationships between variables. Findings revealed that male students' use of the Internet was more problematic compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
8
0
3
Order By: Relevance
“…Salah satu cara untuk mendapatkan persahabatan, dukungan emosional atau untuk mencoba menghindari suasana hati negatif adalah dengan berinteraksi dalam jaringan (online) (Larraaga, Yubero, Ovejero, & Navarro, 2016;Ozgur, Demiralay & Demiralay, 2014). Di sisi lain, ketika remaja menghabiskan waktu untuk berinteraksi secara online di internet dapat meningkatkan sejumlah risiko potensial negatif (Larraaga et al, 2016;Ozgur, Demiralay & Demiralay 2014). Risiko menjadi pelaku perundungan-siber meningkat bila remaja merasa kesepian dalam hubungan dengan keluarga dan orang tua (Guarini et al, 2012).…”
Section: Kesepian Dan Perundungan-siberunclassified
“…Salah satu cara untuk mendapatkan persahabatan, dukungan emosional atau untuk mencoba menghindari suasana hati negatif adalah dengan berinteraksi dalam jaringan (online) (Larraaga, Yubero, Ovejero, & Navarro, 2016;Ozgur, Demiralay & Demiralay, 2014). Di sisi lain, ketika remaja menghabiskan waktu untuk berinteraksi secara online di internet dapat meningkatkan sejumlah risiko potensial negatif (Larraaga et al, 2016;Ozgur, Demiralay & Demiralay 2014). Risiko menjadi pelaku perundungan-siber meningkat bila remaja merasa kesepian dalam hubungan dengan keluarga dan orang tua (Guarini et al, 2012).…”
Section: Kesepian Dan Perundungan-siberunclassified
“…Tales relaciones, como sostienen Beranuy, Chamarro, Graner y Carbonell (2009), tienen por objeto no solo informar sino también comunicar, afectar e influir la vida personal y profesional de los individuos. De este modo, el incremento del uso de Internet en general y del software social en particular, y dentro de este de las redes sociales, han promovido cambios en las estructuras culturales y sociales (Ozgur, Demiralay y Demiralay, 2014;Alonso, Morte y Almansa, 2015), los cuales han generado nuevas formas de entender y sentir la vida, así como de propiciar una mayor accesibilidad a la información, los recursos y las experiencias de los demás internautas (Alonso, Morte y Almansa, 2015; Gómez, Ruíz y Sánchez, 2015). En consecuencia, todo ello contribuye en propiciar una visión más holística de la comunidad en la que se participa, Las redes sociales -nacidas bajo la teoría de los 6 grados de separación-se dibujan como la herramienta que permite estar conectado con nuestros colegas, amigos, conocidos y familiares, además de abrir nuestro mundo de relaciones al infinito.…”
Section: Introductionunclassified
“…Basaran [22] revealed that recreational activities were specified to have positive effect on increasing the self-esteem level and decreasing loneliness level of the prisoners. Ozgur et al [23] found a significant relationship was found between the level of problematic Internet use and loneliness. Ilhan [24] indicated that predictive power of masculinity was significant on loneliness Public and Private University Students in Bangladesh only for men.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Besides measuring the level of real life social network, the study also measures the level of loneliness of students using twenty items UCLA loneliness scale following Rusell, et al [39], Basarn [22], Ozgur et al [23], Penning et al [20] and Ilhan [24]. Among twenty items, there are 10 negatively stated (lonely) and 10 positively stated (non-lonely) items.…”
Section: Ucla Loneliness Scalementioning
confidence: 99%